Water Quality and Performance Assessment of Porous Asphalt Mix Modified Using Charcoal Powder - Kavya Mariya Thomas; Noel Varghese Mathew; Rajalekshmi P R; Rajalekshmi Suresh Kumar; Reebu Zachariah Koshy (Journal of Sustainable Engineering: Proceedings Series, 2019)
Porous pavements are used to allow infiltration of water for increasing ground water storage. Bio char (Charcoal) is a low cost adsorbent used for the removal of heavy metals and other contaminants. This project examines the possibility of using bio char in porous asphalt mixes and efficiency of the asphalt layer modified with charcoal in removing contaminants from typical storm water. Bio char is added by partial replacement of fine aggregates of size less than 2.36 mm. Preliminary Marshall tests indicated that bio char content of about 1to 2 % is not seriously affecting the properties of porous asphalt mix. Marshall test without charcoal has given the optimum binder content as 5 %. Therefore for the study, samples for Marshall tests were prepared keeping the optimum binder content as 5 % and varying the charcoal content as 1, 1.5 & 2 %. From the drain down, air void, flow and stability requirement it was seen that 1.5 % of charcoal is the optimum. Subsequently for the water quality analysis of water infiltrating through the porous asphalt layer samples are prepared using 1.5 % charcoal. Typical storm water is prepared by adding nitrate & chromium to deionized water. Water quality analysis revealed that charcoal modified asphalt layer can remove 97.2 % nitrate, 56 % of chromium from the storm water, and improve the quality of ground water.